2021
DOI: 10.2188/jea.je20190332
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Working Life Years Due to Mortality, Sickness Absence, or Ill-health Retirement: A Comprehensive Approach to Estimating Disease Burden in the Workplace

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Only two studies included three [17] or several [18] exit routes from the labour market in their calculation of YWLL. Disability retirement is a common cause of YWLL [17][18].…”
Section: Indicatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two studies included three [17] or several [18] exit routes from the labour market in their calculation of YWLL. Disability retirement is a common cause of YWLL [17][18].…”
Section: Indicatorsmentioning
confidence: 99%
“…Several different indicators to estimate the length of working life [4,16] or the number of working years lost [17][18][19] have been proposed. However, most of the original studies identified the determinants of a single exit route from employment, such as sickness absence, disability retirement, early retirement, unemployment, non-employment or premature death.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations